PERBANDINGAN EFEK PENYEMBUHAN LUKA BAKAR ANTARA GEL EKSTRAK ETANOL DAUN AFRIKA (Gymnanthemum amygdalinum Del.)DENGAN GEL EKSTRAK ETANOL DAUN KELAPA SAWIT ( Elaeis guineensis Jacq.) SERTA KOMBINASINYA PADA KELINCI TAHUN 2019 - Suventi Syafrina Ginting (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2020)
African leaves (Gymnanthemum amygdalinum Del.) And palm leaves (Elaeis guineensis Jacq.) Have secondary metabolites, namely alkaloids, steroids / terpenoids, flavonoids, tannins, and saponins in this study aimed to determine the effectiveness of healing burns. The extract was made by maceration method using 96% ethanol. This test used 3 rabbits, each of which had been burnt into 6 wound areas on the back of the rabbit. First group (positive control), second group (without treatment), third group gel with Arfika leaf ethanol extract concentration of 5%, fourth group gel with palm ethanol extract concentration of 7.5%, fifth group of groups gel with a combination of Arfika leaf ethanol extract concentration of 5% and 7.5% palm oil leaf ethanol extract The burns that have been made are smeared with as much test preparation as possible once a day. The next day the diameter of the wound was measured, then smeared with an adequate amount of gel. This is done until the diameter of the wound is equal to zero or the wound has been covered by new tissue. The results of testing the effectiveness of healing burns showed that all treatment groups had a faster recovery day compared to negative controls. The conclusion of this study is the combination of 5% arfika ethanol extract gel and 7.5% oil palm leaf ethanol extract is the group with the fastest fastest day on the 19th day.